Effectiveness of Scientific Learning Guided Inquiry Devices Based on Real Media to Improve Understand Concept and Skills Process of Science Students - Susilawati, Susilawati; Doyan, Aris; Artayasa, Putu; Soeprianto, Hary; Harjono, Ahmad; Kartini, Kartini (International Conference on Elementary Education, 2020)
This study aims to develop a science learning device with a guided inquiry model which assisted by real media in improving students’ conceptual understanding and science process skill. The research model uses the 4D (4-D Model) with the stages of define, design, develop and disseminate. Analysis of the results of the effectiveness using the N-gain equation shows that learning devices can improve students' conceptual understanding and science process skills in light material and optical devices. The average percentage of N-gain for students’ conceptual understanding on each sub-materials: shadows on a flat mirror, the nature of shadows on curved mirrors, the nature of shadows on lenses, and optical devices was shown an increase in the percentage of N-gain. This was caused by guided inquiry models assisted by real media which make students directly conduct learning activities and observations. In the aspect of science process skills, the average N-gain in the aspect of predicting and applying concepts has a high N-gain value. The model which used in this research help students to find a concept through experiments and students were directly involved in finding solutions for the problems